Dual-Targeted Autoimmune Sword in Fatal Epilepsy: Patient's glutamate receptor AMPA GluR3B peptide autoimmune antibodies bind, induce Reactive Oxygen Species (ROS) in, and kill both human neural cells and T cells - Levite, Mia; Zelig, Daniel; Friedman, Alon; Ilouz, Nili; Eilam, Raya; Bromberg, Zohar; Ramadhan Lasu, Ally Ahmed; Arbel-Alon, Sagit; Edvardson, Shimon; Tarshish, Mark; Riek, Lul P.; Lako, Richard Lino; et al. (Journal of autoimmunity, 2020)
Nodding Syndrome (NS) is a fatal pediatric epilepsy of unknown etiology, accompanied by multiple neurological impairments, and associated with Onchocerca volvulus (Ov), malnutrition, war-induced trauma, and other insults. NS patients have neuroinflammation, and ~50% have cross-reactive Ov/Leiomodin-1 neurotoxic autoimmune antibodies. Studying 30 South Sudanese NS patients and a similar number of healthy subjects from the same geographical region, revealed autoimmune antibodies to 3 extracellular peptides of ionotropic glutamate receptors in NS patients: AMPA-GluR3B peptide antibodies (86%), NMDA-NR1 peptide antibodies (77%) and NMDA-NR2 peptide antibodies (87%) (in either 1:10, 1:100 or 1:1000 serum dilution). In contrast, NS patients did not have 26 other well-known autoantibodies that target the nervous system in several autoimmune-mediated neurological diseases. We demonstrated high expression of both AMPA-GluR3 and NMDA-NR1 in human neural cells, and also in normal human CD3+ T cells of both helper CD4+ and cytotoxic CD8+ types. Patient's GluR3B peptide antibodies were affinity-purified, and by themselves precipitated short 70 kDa neuronal GluR3. NS patient's affinity-purified GluR3B peptide antibodies also bound to, induced Reactive Oxygen Species (ROS) in, and killed both human neural cells and T cells within 1-2 hours only. NS patient's purified IgGs, or serum (1:10 or 1:30), induced similar effects. In vivo video EEG experiments in normal mice, revealed that when NS patient's purified IgGs were released continuously (24/7 for 1 week) in normal mouse brain, they induced all the following: 1.Seizures, 2. Cerebellar Purkinje cell loss, 3. Degeneration in the hippocampus and cerebral cortex, and 4. Elevation of CD3+ T cells, and of activated Mac-2+microglia and GFAP+astrocytes in both the gray and white matter of the cerebral cortex, hippocampus, corpus calossum and cerebellum of mice. NS patient's serum cytokines: IL-1β, IL-2, IL-6, IL-8, TNFα, IFNγ, are reduced by 85–99% compared to healthy subjects, suggesting severe immunodeficiency in NS patients. This suspected immunodeficiency could be caused by combined effects of the: 1. Chronic Ov infection, 2. Malnutrition, 3. Killing of NS patient's T cells by patient's own GluR3B peptide autoimmune antibodies (alike the killing of normal human T cells by the NS patient's GluR3B peptide antibodies found herein in vitro). Regardless of NS etiology, NS patients suffer from ‘Dual-targeted Autoimmune Sword’: autoimmune AMPA GluR3B peptide antibodies that bind, induce ROS in, and kill both neural cells and T cells. These neurotoxic and immunotoxic GluR3B peptide autoimmune antibodies, and also NS patient's NMDA-NR1/NR2A and Ov/Leiomodin-1 autoimmune antibodies, must be silenced or removed. Moreover, the findings of this study are relevant not only to NS, but also to many more patients with other types of epilepsy, which have GluR3B peptide antibodies in serum and/or CSF. This claim is based on the following facts: 1. The GluR3 subunit is expressed in neural cells in crucial brains regions, in motor neurons in the spinal cord, and also in other cells in the body, among them T cells of the immune system, 2. The GluR3 subunit has diverse neurophysiological role, and its deletion or abnormal function can: disrupt oscillatory networks of both sleep and breathing, impair motor coordination and exploratory activity, and increase the susceptibility to generate seizures, 3. GluR3B peptide antibodies were found so far in ~27% of >300 epilepsy patients worldwide, which suffer from various other types of severe, intractable and enigmatic epilepsy, and which turned out to be 'Autoimmune Epilepsy'. Furthermore, the findings of this study could be relevant to different neurological diseases besides epilepsy, since other neurotransmitter-receptors autoantibodies are present in other neurological and psychiatric diseases, e.g. autoimmune antibodies against other GluRs, Dopamine receptors, GABA receptors, Acetylcholine receptors and others. These neurotransmitter-receptors autoimmune autoantibodies might also act as ‘Dual-targeted Autoimmune Sword’ and damage both neural cells and T cells (as the AMPA-GluR3B peptide antibodies induced in the present study), since T cells, alike neural cells, express most if not all these neurotransmitter receptors, and respond functionally to the respective neurotransmitters - a scientific and clinical topic we coined 'Nerve-Driven Immunity'. •Patients with Nodding Syndrome or some other intractable epilepsies, have pathological AMPA GluR3B peptide autoimmune antibodies.•Patient’s GluR3B antibodies target the central AMPA receptor for Glutamate – the major excitatory neurotransmitter in the brain.•Patient’s GluR3B peptide antibodies bind, induce ROS production in, and kill rapidly both neural cells and T cells.•Patient’s IgG induce in normal mice: epileptic seizures and multiple brain damage resembling that of NS patients.•Patient’s IgG elevate in normal mice: CD3 +T cells, activated microglia and activated astrocytes. One Sentence Summary: Glutamate receptor autoimmune antibodies: AMPA GluR3B peptide antibodies of patients with fatal epilepsy: Nodding Syndrome, induce production of Reactive Oxygen Species in, and kill both, neural cells and T cells. These findings are very relevant to many more patients with other types of epilepsy which have these GluR3B peptide antibodies in serum and/or CSF.